Impact of Heat Input on the Cladding of Super Austenitic Stainless Steel Through the Gas Tungsten Arc Welding Process on ASTM A516 Grade 70 Steel - da Cruz Junior, Eli Jorge; Varasquim, Francisco M. F. A.; De Mendonça, Vagner Romito; Ventrella, Vicente A. [UNESP]; Gonçalves, Aparecido Carlos [UNESP]; Fagundes Junior, José Gedael [UNESP]; Zambon, Andrea; Calliari, Irene (MDPI, 2024)
The cladding process reduces manufacturing costs by depositing super austenitic stainless steel onto low-carbon steel. Arc welding techniques, especially gas tungsten arc welding (GTAW), are commonly used for this purpose. This study evaluates the influence of heat input on cladding performance. Macroscopic analysis showed good fusion of the weld beads to the base metal with no defects. Higher heat input resulted in a lower dilution rate due to increased reinforcement. A microstructural analysis of the heat-affected zones revealed similar characteristics, with martensite formation attributed to cooling conditions. Increased microhardness was observed at the interface between the cladding and base metal, corroborating the microstructural findings. Additionally, a significant enhancement in corrosion resistance was noted in the deposited layers. This research contributes to optimizing cladding processes, ensuring better material performance in industrial applications.
Keywords: corrosion resistance; GTAW; low-carbon steel; microhardness; microstructure; super austenitic stainless steel